Demoralization and Remoralization: The Power of Creating Space for Teachers’ Moral Centres - Santoro, Doris; Hazel, Julia (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2022)
In this collaborative analysis, we (a philosopher of education and an experienced public school educator) examine the experience of demoralization and remoralization in the context of the COVID-19 pandemic. We overlay the context of the pandemic with the context of institutional racism and their interwoven impact for educators of colour. We use one educator’s narratives about teaching during the pandemic as a launching point about where philosophical research on teacher demoralization needs to go next. We argue that the pandemic presents an opportunity for teachers to gain clarity about their moral centres and for school and district leaders to create space for teachers to enact their professional values and thus access the moral rewards of their work. Teachers of colour encounter distinct challenges in having their moral centres recognized, but their prior experiences with moral friction may present them with unique resources in these challenging times. Teachers’ energy and agency are squandered, leading to demoralization, if they are not given sufficient space to enact their professional values.